Scalable-Designed Photonic Metamaterial for Color-Regulating Passive Daytime Radiative Cooling - Yu, Xiao‑Qing; Li, Fucheng; Wang, Jiawei; Zhang, Nianxiang; Li, Guo‑Xing; Song, Yan; Li, Qing; Chen, Su (Nano-Micro Letters, 2026)
Methods allowing passive daytime radiative cooling (PDRC) to be carried out in an energy-efficient and scalable way are potentially important for various disciplines. Here, we report a sustainable strategy for scalable-designed and color-regulating PDRC coating based on high-crystallinity photonic metamaterial (crystallinity: 71.5%; enhanced assembly efficiency: 72%), that is derived from the as-prepared 55 wt% solid content poly(methyl methacrylate-butyl acrylate-methacrylic acid) P(MMA-BA-MAA) monodispersed latexes (approaching theoretical limit: 59 wt%). Robust meter-scale PDRC coatings are constructed by various industrial modes onto diverse surfaces, addressing bottlenecks like dull appearance, high cost, low efficiency, and hard construction. Notably, the solar reflectance, long-wave infrared emittance, and calculated theoretical cooling power of the designed PDRC coating, respectively, reach 0.94, 0.97, and 95.5 W m−2 under solar radiation, which can achieve an average 5.3 °C sub-ambient daytime temperature drop in the summer in Nanjing. The cooling performance, scale preparation, and cost-effectiveness of the PDRC coating have extended into leading position compared with those of state-of-the-art designs. This work provides promising route to reduce carbon emissions and energy consumption for global sustainability. Highlights: 1 The 55 wt% solid content monodispersed latexes were synthesized under the synergistic action of ionic and nonionic surfactants. 2 The 55 wt% solid content monodispersed latexes open a homogeneous assembly avenue, establishing high-crystallinity photonic metamaterial (crystallinity:71.5%). 3 We developed scalable-designed and color-regulating passive daytime radiative cooling coating based on the high-crystallinity photonic metamaterial, showing high solar reflectance ( 0.94), high infrared emittance ( 0.97), large sub-ambient cooling temperature (average 5.3 °C), and great cooling power ( 95.5 W m−2).